(untitled) (American Journal of Islam and Society, 1994)
The first paper in our present issue is by Abdullah H. M. a1 Khalifah and examines how religiosity in an Islamic context serves as a protective mechanism against criminal temptation. This is done, in short, by placing the concept of law in the realm of religion, which means that criminal activity is seen as a violation of God’s law before it is seen as a violation of a person’s rights. Such a perspective also reinforces the awareness of the certainty and severity of punishment in the afterlife. The author argues that Islam provides a unique social control perspective, one that has accounted for the main parameters that underlie the mechanisms of social control: religion, morality, and law. He first reviews the theories and literature concerning the religion-crime relationship and then proceeds to discuss the meaning of religiosity in Islam and how it has been transformed into a valuable force for crime control. He concludes his analysis with a discussion of the elements of Islamic ideology that constrain criminal behavior. Muhammad al-Ghazali calls for a study of Sh& Wali Allah’s thought in greater depth, for the exceptionally futuristic thrust of his ideas are extremely relevant and promising for contemporary and future Islamic thought. He chooses to study Shah Wali Allah’s synthesis of reason, revelation, and empiricism, which he claims has been unrecognized by many earlier and contemporary scholars. Al-Ghazali shows how Shah Wali All& builds evidence from an inductive survey of social phenomena to substantiate the contentions of revelation while remaining within the doctrinal framework of revealed guidance and thus constructs a paradigm of universal social culture. Also covered is Shah Wali Allah’s analysis of what separates human beings from animals and how the former, due to their inherent and God-given instincts, develop civilization. Muhammad Hashim Kamali discusses the possibility of price control (tus‘fr) in Islam law. He shows that Islam did not promulgate any law that limits profits and fixes prices. He also examines several provisions concerning price control and highlights some of the conflicting interests of freedom vs. authority that are reflected in relevant Shari‘ah provisions. The underlying issue of his research is the extent to which price controls may or may not impinge on the basic freedom of trade and of the individual to sell items at the regular market price as opposed to one fixed ...